Proposal for an environmental health indicator (ISA) for sanitation analysis on the Federal University of Sergipe campus-São Cristóvão, Brazil (Research, Society and Development, 2021)
In Brazil, there is a great deficiency when it comes to drinking water supply, sewage collection and treatment, collection and correct disposal of solid waste, as well as better management of water resources and care for public health in urban centers. There are several laws, ordinances and resolutions that determine how these services should be offered to people, however, more than half of the Brazilian population does not have these rights ensured, finding themselves in unhealthy situations. Because of this, the State Sanitation Council in the State of São Paulo (CONESAN), in 1999, created a model that allowed local authorities to assess the environmental health of a given region. Thus, the present study aimed to assess, based on the adaptation of the CONESAN methodology, the health condition of the University city Prof. José Aloísio de Campos, located in São Cristóvão SE. Adaptation was necessary due to local specificities and due to the focus of the research being strongly based on basic sanitation on campus. The environmental health indicator for this study was called ISA-UFS, which considered as specific sub-indicators: Water Supply, Solid Waste, Sanitary Sewage, Urban Drainage and Vector Control. From the results obtained, it was possible to interpret the current sanitation situation of the campus to a condition of Medium Health (ISA-UFS = 0.66), with potential for improvement after making simple changes in sanitation services such as daily cleaning of roads and increased frequency of solid waste collection.